Inside the visible; an elliptical traverse of 20th century art in, of, and from the feminine. - Zegher, C. De (Gent : La Chambre, 1996)
Bourgeois, Louise ; Cahun, Claude ; Carr, Emily ; Cha, Thesesa Hak Kyung ; Clark, Lygia ; Darboven, Hanne ; Dujourie, Lili ; Gallagher, Ellen ; Gego ; Hatoum, Mona ; Hervieux, Nathalie ; Hesse, Eva ; Hiller, Susan ; Höch, Hannah ; Janssens, Ann Veronica ; Kobro, Katarzyna ; Kusama Yayoi ; Lichtenberg-Ettinger, Bracha ; Maiolino, Anna Maria ; Martin, Agnes ; Mendieta, Ana ; Newman, Avis ; Rama, Carol ; Bosler, Marthe ; Salomon, Charlotte ; Schendel, Mira ; Silverman, Lynn ; Spero, Nancy ; Sterbak, Jana ; Taeuber-Arp, Sophie ; Tasseel, Nadine ; Torfs, Ana ; Tuerlinckx, Joëlle ; Vicuña, Cecilia ; Vieira da Silva, Maria Elena ; Weems, Carrie Mae ; Woodman, Francesca
kunstcatalogus